Decoupling the impact of biodiversity and environmental factors on the biomass and biomass growth of trees in subtropical forests. (31st March 2022) - Tiwari, Ravi Mohan; Liu, Jinliang; Xie, Yuchu; Yao, Shenhao; Liu, Shenglong; Wu, Sumei; Liu, Julian; Qian, Haiyuan; Lei, Zupei; Zhang, Hongwei; Zhong, Lei; Wei, Boliang; et al.
Abstract: The relationship between biodiversity and ecosystem functioning has become a central issue in any forest ecosystem. However, there are few studies on the interaction of environmental factors based on the history of subtropical forest disturbance. In this study, we intended to disentangle the relationship between different aspects of biodiversity and biomass or biomass change when considering the environmental factors of 34 subtropical forest plots in Zhejiang Province, eastern China. We used linear models to analyze the effects of taxonomic, functional and phylogenetic diversity at the plot level of tree biomass and its growth with or without environmental factors. Taxonomic diversity and functional diversity, rather than phylogenetic diversity, showed significant correlations with biomass and biomass growth. We further found that there was a positive linear relationship between biomass or biomass growth and mean annual temperature and altitude. In addition, the relationship between biomass growth and functional diversity was significantly stronger than the relationship between biomass growth and phylogenetic diversity or taxonomic diversity when environmental factors and stand developmental stages were considered. Our results suggested that the relationship between biodiversity and ecosystem functioning is dependent upon the selection of diversity index and environmental conditions.